Pastoral care and counselling in current times: Relevance and context of care - Glenda A. Dames; Gordon E. Dames (HTS Teologiese Studies/Theological Studies)
Since the inception of the Pastoral Care Movement, the approach to pastoral care has evolved from the traditional shepherd model to a more clinical, client-centred method. This evolution requires a thorough analysis of recent trends and dynamics in pastoral care, especially in relation to key theological theories and the Church’s role in providing support. Today, the landscape of pastoral care covers a range of topics, including ecotheology, global existential crises and the Church’s involvement in addressing these issues. Additionally, this examination reveals conclusions about theological shortcomings and inconsistencies in emphasis within pastoral care.